A 2D model for prediction of nanoparticle distribution and microstructure evolution during solidification of metal matrix nanocomposites. (2nd August 2021) - M, Jegatheesan; Bhattacharya, Anirban
Abstract: A 2D numerical model to predict the microstructure evolution in binary alloy matrix nanocomposites is presented. The main novelty of the model is that it captures the effect of nanoparticles on binary alloy dendrite growth and microstructure evolution. Diffusion based transport of nanoparticles is solved using a nanoparticle concentration defined in a similar way to an alloying element. Engulfment or rejection of nanoparticles at the solidification interface is implemented by defining a partition coefficient. The diffusivity of nanoparticles is calculated based on nanoparticle movement due to Brownian motion. The governing equations for binary alloy solidification are formulated using the volume averaged enthalpy method with a probabilistic nucleation model for grain nucleation. The effect of nanoparticles on solidification is incorporated through modifications of the solute diffusion field and interfacial energy. The developed model is used for predicting the effect of nanoparticle concentration and nanoparticle radius on dendrite growth and microstructure evolution. From single dendrite study, it is observed that the dendrite size decreases with increase in nanoparticle concentration while it increases with increase in nanoparticle radius. During microstructure evolution, increased non-homogeneity in nanoparticle distribution is observed with increase in nanoparticle concentration and more uniform distribution is observed with increase in nanoparticle radius.